2019
DOI: 10.1002/adfm.201901154
|View full text |Cite
|
Sign up to set email alerts
|

Ru–Ru2PΦNPC and NPC@RuO2 Synthesized via Environment‐Friendly and Solid‐Phase Phosphating Process by Saccharomycetes as N/P Sources and Carbon Template for Overall Water Splitting in Acid Electrolyte

Abstract: Although numerous ruthenium-based phosphates possess high catalytic activities for hydrogen evolution reaction (HER), most of them rely on dangerous and toxic synthesis routes. Biological slices confirm that Ru ions can penetrate the cell walls of saccharomycete, which facilitates the adsorption of Ru ions. Herein, based on a green synthesis process by saccharomycete cells as the carbon template and nitrogen/phosphorus (N/P) sources, novel Janus-like rutheniumruthenium phosphide nanoparticles embedded into a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(45 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…© 2020 Wiley-VCH GmbH yeast, PCl 3 , etc. [184][185][186][187][188][189][190][191][192] Furthermore, Table 2 lists the typical advantages and disadvantages of preparing TMPs based on phosphorus sources.…”
Section: (11 Of 23)mentioning
confidence: 99%
See 1 more Smart Citation
“…© 2020 Wiley-VCH GmbH yeast, PCl 3 , etc. [184][185][186][187][188][189][190][191][192] Furthermore, Table 2 lists the typical advantages and disadvantages of preparing TMPs based on phosphorus sources.…”
Section: (11 Of 23)mentioning
confidence: 99%
“…[189] Similarly, Zhou and co-workers reported saccharomycete cells as both carbon template and green biomass phosphorus source to safely synthesize the Janus-like Ru-Ru 2 P nanoparticles embedded into nitrogen, phosphorus dual-doped carbon as an efficient electrocatalyst for HER. [188] Pyrolysis of phosphorusbased porous polymer precursors and metal-containing anions precursor is another way to obtain TMPs. [235] In addition, the ionic liquid was reported as the phosphorus precursor to prepare TMPs.…”
Section: (18 Of 23)mentioning
confidence: 99%
“…Undoubtedly, the S-RuP@NPSC-900 possessed overwhelming advantage in current density after normalized by Ru loading, which revealed the high utilization of Ru. Comparing with current relevant literature with the overpotential of 50 mV, the HER mass specific activity of S-RuP@NPSC-900 (871.50 A g −1 ) with an ultralow loading of Ru (0.8 wt%) was larger than those of the recently reported Ru-based HER electrocatalysts, such as RuP 2 @NPC (64.38 A g −1 ), [47] Ru-Ru 2 PΦNPC (2.96 A g −1 ), [40] RuP/CC (38.40 A g −1 ), RuP 2 /CC(7.69 A g −1 ), [41] and the ultrasmall Ru 2 P NPs@GO (765.63 A g −1 ), [48] which showed that S-RuP@NPSC-900 was a promising and competitive HER catalyst.…”
Section: Resultsmentioning
confidence: 58%
“…In addition, PZS used as solid phosphorus source replaced the gas phosphating reaction using the hypophosphites [31] and hydrothermal reaction using red phosphorus or trioctylphosphine (TOP) [38,39] to avoid producing toxic, flammable polluting tail gas. [40] The obtained S-RuP@NPSC as HER electrocatalyst possessed the high catalytic activity with an overpotential of 92 mV to reach a current density of 10 mA cm −2 and rough catalytic stability in alkaline solution. It is worth noting that the S-RuP@NPSC possessed high utilization of Ru precious metals, the according mass specific activity was 22.88 times than that of 20% Pt/C with the overpotential of 250 mV.…”
Section: Introductionmentioning
confidence: 95%
“…As shown in Figure S13c and S14d, Cl-Pt-O-Ru and Pt-O-Ce seem to be the favorable active site for HER since its DG H* value (0.095 and 0.034 eV, respectively) are closer to zero than the corresponding values for Pt-O-Ru (site-A, À0.15 eV). [17] However, when a catalyst contains more than one kind of active site, the hydrogen spillover effect between different sites, namely the H* transfer from a hydrogen-enriched phase (more negative DG H* ) to a hydrogen-deficient phase (more positive DG H* ), can greatly affect the overall catalytic activity. Therefore, we also calculated the DG H* values for the possible adjacent sites: the calculated values for the O atom in Pt-O-Ru (site-B), RuO 2 (110) plane (site-C), Ce-O-Pt, and CeO 2 (111) plane were À0.014, 0.23, 0.04, and À0.34 eV, respectively (Figure S13 and S14).…”
mentioning
confidence: 99%